Multispecies justice: Climate‐just futures with, for and beyond humans. (28th December 2020) - Tschakert, Petra; Schlosberg, David; Celermajer, Danielle; Rickards, Lauren; Winter, Christine; Thaler, Mathias; Stewart‐Harawira, Makere; Verlie, Blanche
Abstract: In 2019, the climate emergency entered mainstream debates. The normative frame of climate justice as conceived in academia, policy arenas, and grassroots action, although imperative and growing in popularity across climate movements, is no longer adequate to address this emergency. This is for two reasons: first, as a framing for the problem, current notions of climate justice are insufficient to overcome the persistent silencing of voices belonging to multiple "others"; and second, they do not question, and thus implicitly condone, human exceptionalism and the violence it enacts, historically and in this era of the Anthropocene. Therefore, we advocate for the concept of multispecies justice to enrich climate justice in order to more effectively confront the climate crisis. The advantage of reconceptualizing climate justice in this way is that it becomes more inclusive; it acknowledges the differential histories and practices of social, environmental, and ecological harm, while opening just pathways into uncertain futures. A multispecies justice lens expands climate justice by decentering the human and by recognizing the everyday interactions that bind individuals and societies to networks of close and distant others, including other people and more‐than‐human beings. Such a relational lens provides a vital scientific, practical, material, and ethical road map for navigating the complex responsibilities and politics in the climate crisis. Most importantly, it delineates what genuine flourishing could mean, what systemic transformations may involve (and with whom), how to live with inevitable and possibly intolerable losses, and how to prefigure and enact alternative and just futures. This article is categorized under: Climate, Nature, and Ethics > Climate Change and Global Justice Abstract : Navigating multispecies justice toward climate‐just futures.